The advantage : why organizational health trumps everything else in business - Lencioni, Patrick, 1965- (Jossey-Bass, 2012)
"There is a competitive advantage out there, arguably more powerful than any other. Patrick Lencioni argues that the seminal difference between successful companies and mediocre ones has little to do with what they know and how smart they are and more to do with how healthy they are. Simply put, an organization is healthy when it is whole, consistent and complete, when its management, operations and culture are unified. Healthy organizations outperform their counterparts, are free of politics and confusion and provide an environment where star performers never want to leave. The Advantage provides a foundational construct for conducting business in a new way--one that maximizes human potential and aligns the organization around a common set of principles"--